An Empirical Study on the Environmental Effects of Agricultural Value-Added, Industrialization, and Economic Growth in Turkey - Koç, Özgür Emre; Koç, Neslihan; Çiçek, Uğur; Bıtrak, Orhan Orçun (International Journal of Energy Economics and Policy, 2025)
In this study, the effects of economic growth, industrialization and agricultural value added on carbon emissions in Turkey were examined within the framework of the Environmental Kuznets Curve (EKC) hypothesis. In the analysis, the validity of the EKC hypothesis was tested with the ARDL (autoregressive distributed lag) model using annual data for the period 1968-2020. The findings show that there is a cointegration relationship between the variables and that in the long term, economic growth initially increases carbon emissions while decreasing them after a certain threshold level. This result reveals that the EKC hypothesis is valid for Turkey. In addition, it was determined that industrialization increases carbon emissions in the long term, while agricultural value added reduces emissions. The results show that agricultural value added reduces carbon emissions in Turkey. This situation can be interpreted as the limited mechanization in agricultural activities and the relatively high prevalence of sustainable agricultural practices. It was determined that industrialization has an increasing effect on carbon emissions. This finding indicates that the industrialization process in Turkey can have a largely energy-intensive and fossil fuel-based structure. Therefore, substituting fossil fuel-based industrial activities with environmentally friendly, renewable energy sources can both increase environmental sustainability and support the economic growth of Turkey, which is largely dependent on foreign energy.